PENGARUH SUDUT PENGAPIAN DAN DURASI INJEKSI ECU ARDUINO TERHADAP KINERJA DAN EMISI GAS MOTOR FI - Muhamad Andito Yogatama; Taufik Wisnu Saputra; Danar Susilo Wijayanto (Scientific Journal of Mechanical Engineering Kinematika, 2025)
The increasing number of motorcycles in Indonesia, exceeding 125 million units in 2022, reflects the high demand for efficient and environmentally friendly vehicles. This trend drives the advancement of combustion system technology, notably the shift from carburetors to Electronic Fuel Injection (EFI). EFI is an electronically controlled fuel delivery system designed to optimize combustion through precise control of ignition timing and fuel injection duration. This system has proven effective in improving engine efficiency and reducing exhaust emissions. However, most mass-produced motorcycles are still equipped with non-programmable ECUs, limiting tuning flexibility. This study evaluates the use of an Arduino-based programmable ECU as a more adaptive alternative. Experiments were conducted on a Honda Vario 110cc FI, varying ignition timing (+2°, +4°, +6°, +8°, +10° BTDC) and fuel injection duration (+5%, +10%, +15%) using Pertamax RON 92 fuel. The results showed an 8% increase in maximum torque (16.98 N.m) at +4° and +5% configuration, and a 3% increase in maximum power at +2° and +10%. The lowest HC and CO emissions were recorded at +2° and +5%, with reductions of 44% and 41%, respectively. The Arduino-based ECU effectively enhances engine performance while maintaining emission efficiency.